The contemporary growth regime has been ensured by the Australian state's mutations (at least until now) - Chester, Lynne (CAER and IRRC, 2008)
With the ascendancy of neoliberalism, the Australian state has not only remained strongly interventionist but has also expanded its sphere of influence and scope of activity. This is contrary to claims of a reduced, withered or slimmed neoliberal state. The Australian state’s interventions have become increasingly varied in the overwhelming pursuit of structural competitiveness. It has developed an extensive ‘micro-structuring’ role, particularly through the creation of new regulatory instruments and institutions, but has not relinquished its economic ‘macro-structuring’ role notwithstanding changes to macroeconomic policy priorities. The Australian state’s interventions have shaped all institutional forms comprising the mode of regulation that guides and supports the accumulation regime. This article discusses the reconfiguration of the Australian state and the forms of its ongoing interventions which have secured and sustained the contemporary growth regime.